Determination of torques at upper limb joints during jumping in badminton smash via kane's method - Ariff, F. H. M.; Rambely, A. S. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The paper discusses determination of torque forces at the upper limb joints, namely shoulder, elbow and wrist, using 2-dimensional Kane`s mathematical model of a three-link system, comprises of upper arm, lower arm and hand-racket segments. A planar threelink kinematic chain model is developed and the inverse dynamic method is applied. Kinematic data from 2 professional badminton players in a Thomas Cup`s Tournament are taken as input in the dynamics equation and torques calculated. The result shows that the elbow joint produced the highest value of torque during contact while performing the jumping smash activity.